Pengembangan Model Governance Digital Untuk Meningkatkan Efisiensi Operasional PLN - Muthia Fadhilla; Syamsir Syamsir; Pretty Novita Zai; Nabila Siti Aqilah; Silvina Maharani Putri; Vinny Meiska Putri; Agil Kurniawan Norza; Rayhan Febi Setiawan (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
In this era of globalization, the development of technological systems greatly influences company business processes. E-Government is a solution to overcome the problems of a public service system which is known to be slow and expensive. This research aims to determine the development of the Digital Governance model to improve PLN's operational efficiency at PT. PLN (Persero) UP3 Padang. The research method used in this research is a qualitative approach with descriptive research type. Data collection techniques are carried out through observation. The results of this research show the development of a digital governance model at PLN providing digital services known as PLN Mobile as well as other programs such as the Yantek Optimization program. In its implementation, of course these services have obstacles such as a lack of public understanding of existing technology. Therefore, PLN is overcoming this by providing counters at PLN service offices which are available 24 hours and the public can contact them by telephone at number 123.